Saliva as a sampling matrix for therapeutic drug monitoring of gentamicin in neonates: A prospective population pharmacokinetic and simulation study. Issue 4 (7th November 2021) - Samb, Amadou; Kruizinga, Matthijs; Tallahi, Younes; van Esdonk, Michiel; van Heel, Willemijn; Driessen, Gertjan; Bijleveld, Yuma; Stuurman, Rik; Cohen, Adam; van Kaam, Anton; de Haan, Timo R; Mathôt, Ron
Abstract : Aims: Therapeutic drug monitoring (TDM) of gentamicin in neonates is recommended for safe and effective dosing and is currently performed by plasma sampling, which is an invasive and painful procedure. In this study, feasibility of a non‐invasive gentamicin TDM strategy using saliva was investigated. Methods: This was a multicentre, prospective, observational cohort study including 54 neonates. Any neonate treated with intravenous gentamicin was eligible for the study. Up to eight saliva samples were collected per patient at different time‐points. Gentamicin levels in saliva were determined with liquid chromatography tandem mass‐spectrometry (LC–MS/MS). A population pharmacokinetic (PK) model was developed using nonlinear mixed‐effects modelling (NONMEM) to describe the relation between gentamicin concentrations in saliva and plasma. Monte Carlo simulations with a representative virtual cohort ( n = 3000) were performed to evaluate the probability of target attainment with saliva versus plasma TDM. Results: Plasma PK was adequately described with an earlier published model. An additional saliva compartment describing the salivary gentamicin concentrations was appended to the model with first‐order input (k13 0.023 h −1 ) and first‐order elimination (k30 0.169 h −1 ). Inter‐individual variability of k30 was 38%. Postmenstrual age (PMA) correlated negatively with both k13 and k30 . Simulations demonstrated that TDM with four saliva samples was accurate in 81% of the simulated cases versus 94% when performed with two plasma samples and 87% when performed with one plasma sample. Conclusion: TDM of gentamicin using saliva is feasible and the difference in precision between saliva and plasma TDM may not be clinically relevant, especially for premature neonates.